REMBESAN MIGAS DI DAERAH TIMOR BARAT (The Oil and Gas Seepages in West Timor ) - Jonathan S. Hadimuljono; Desi Yensusnimar; Ario B Wicaksono; Suliantara Suliantara (BBPMGB LEMIGAS, 2016)
Di daerah Timor Barat banyak dijumpai rembesan migas (hidrokarbon) yang pada umumnya berasosiasi dengan semburan lumpur atau mud volcano. Rembesan gas hidrokarbon dijumpai di setiap lokasi mud volcano, sedangkan rembesan minyak hanya pada lokasi mud volcano di bagian selatan Pulau Timor. Di beberapa tempat, kadang kadang rembesan minyak dan gas juga dijumpai pada sumur yang digali oleh penduduk untuk mencari air. Kandungan gas hidrokarbon dominan terdiri dari metana (CH4) dengan sedikit etana (C2H6) dan kandungan nitrogen (N2) yang cukup tinggi yang menunjukkan karakter rembesan. Analisis Gas Chromatography (GC) pada rembesan minyak dalam lumpur menunjukkan kemungkinan minyak berasal dari batuan sedimen yang diendapkan pada lingkungan lacustrine atau transisi-laut.There are many oil and gas (hydrocarbons) seepages have been found in West Timor area, and generally they are associated with mud volcanoes or mud flow. The gas seepages occurred in every mud volcano location in West Timor, while the seepage of oil only found at mud volcanoes in Southern part of West Timor area. In some places, sometimes the seepage also exists in well that drilled by local people for water. The gas seepage dominantly composes of methane (CH4) and minor ethane (C2H6) with high nitrogen (N2) content which indicates seepage characteristic. Gas Chromatography (GC) analysis of oil seepages revealed that the oil probably originated from lacustrine or marine-transition sedimentary environments.